Ответы и объяснения

2013-10-28T17:16:52+04:00
(38+z)-64=102           38+(z-64)=102
38+z=102+64             z-64=102-38
38+Z=166                   z-64=64
z=166-38                    z=64+64
z=128                         z=128
73-(25+a)=29                  73-(а+29)=25
25+a=73-29                     а+29=73-25
25+a=44                         а+29=48
a=44-25                          а=48-29
a=19                               а=19
(25-a)-47=50                   25+(а-47)=50
25-a=50+47                    а-47=50-25
25-a=97                          а-47=25
a=97-25                         а-47=25+47
a=72                              а=72